2019
DOI: 10.1017/s0033291719001028
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the occurrence of distressing involuntary memories following propranolol or hydrocortisone in healthy women

Abstract: BackgroundPharmacological treatments targeting the neuroendocrine stress response may hold special promise in secondary prevention of posttraumatic stress disorder (PTSD). However, findings from clinical trials have been inconsistent and the efficacy of specific drugs, their temporal window of efficacy, effective doses and the characteristics of likely treatment responders remain unclear.MethodUsing an experimental human model of distressing involuntary memory formation, we compare the effects of two drugs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
2
11
1
Order By: Relevance
“…Elevated catecholamine secretion has been implicated in excessive consolidation of traumatic memories, which is substantial for the development and maintenance of re-experiencing symptoms of PTSD such as intrusive memories, flashbacks, and repetitive nightmares [68,69]. Importantly, the administration of pharmacological agents such as β-blockers immediately after trauma exposure, might be helpful as secondary preventive agents for the development of specific PTSD symptoms [69,70].…”
Section: Locus Ceruleus/autonomic Nervous System (Lc/ans)mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated catecholamine secretion has been implicated in excessive consolidation of traumatic memories, which is substantial for the development and maintenance of re-experiencing symptoms of PTSD such as intrusive memories, flashbacks, and repetitive nightmares [68,69]. Importantly, the administration of pharmacological agents such as β-blockers immediately after trauma exposure, might be helpful as secondary preventive agents for the development of specific PTSD symptoms [69,70].…”
Section: Locus Ceruleus/autonomic Nervous System (Lc/ans)mentioning
confidence: 99%
“…Clinical symptoms of PTSD may thus be attributed to cortisol decrease that fails to shut down the catecholarminergic response in limbic structures. It has been suggested that an exaggerated catecholamine secretion is related to excessive consolidation of traumatic memories, which in turn may lead to the development and maintenance of PTSD symptoms, such as intrusive thoughts, flashbacks, and repetitive nightmares [67,68,70]. By contrast, glucocorticoids impair or have little effect on memory consolidation in the absence of arousal-induced noradrenergic activation [69,100].…”
Section: The Longitudinal Course Of Pediatric Ptsd After Accidentsmentioning
confidence: 99%
“…Because synaptic consolidation is a brief (<6 hr), protein synthesis-dependent process, commonly used drugs with down-stream protein synthesis-inhibiting effects, such as beta-blockers or NMDA receptor antagonists, have theoretical potential as secondary preventive agents. However, currently, neither meta-analyses of clinical trials [ 4 , 5 ] nor experimental studies [ 6 ] (but see [ 7 ]) support use of beta-blockers, and only indirect experimental [ 8 ] or cross-sectional [ 9 ] evidence on NMDAR antagonists currently exists.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies allow pathogenic memory phenomena (e.g., distressing involuntary memories [ 14 ]) to be modelled and assessed, while limiting the influence of numerous sources of statistical noise common in clinical studies. Two such translational studies have modelled preventative treatment for PTSD with hydrocortisone administered before [ 15 ] or shortly after [ 7 ] an analogue trauma (a distressing film). Only the latter study demonstrated a reduction in the number of intrusions relative to placebo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation